Quantitative determination of the lateral density and intermolecular correlation between proteins anchored on the membrane surfaces using grazing incidence small-angle X-ray scattering and grazing incidence X-ray fluorescence - Abuillan, Wasim; Tanaka, Motomu (The journal of chemical physics, 2012)
As a physical model of the surface of cells coated with densely packed, non-crystalline proteins coupled to lipid anchors, we functionalized the surface of phospholipid membranes by coupling of neutravidin to biotinylated lipid anchors. After the characterization of fine structures perpendicular to the plane of membrane using specular X-ray reflectivity, the same membrane was characterized by grazing incidence small angle X-ray scattering (GISAXS). Within the framework of distorted wave Born approximation and two-dimensional Percus-Yevick function, we can analyze the form and structure factors of the non-crystalline, membrane-anchored proteins for the first time. As a new experimental technique to quantify the surface density of proteins on the membrane surface, we utilized grazing incidence X-ray fluorescence (GIXF). Here, the mean intermolecular distance between proteins from the sulfur peak intensities can be calculated by applying Abelé's matrix formalism. The characteristic correlation distance between non-crystalline neutravidin obtained by the GISAXS analysis agrees well with the intermolecular distance calculated by GIXF, suggesting a large potential of the combination of GISAXS and GIXF in probing the lateral density and correlation of non-crystalline proteins displayed on the membrane surface.